Sign- and goal-tracking rats show differences in various executive functions - Enkel, Thomas; Bartsch, Dusan; Bähner, Florian (Behavioural brain research, 2019)
Sign tracking (ST) is a complex Pavlovian trait that is known to impact instrumental behaviour. Recent work suggests that this trait also correlates with altered top-down executive control relative to goal tracking (GT) rats. This raises the question as to the extent to which both phenotypes differ in executive functions. Moreover, it is unclear which cognitive processes might cause potential differences between ST and GT rats. We therefore compared the behaviour of ST and GT rats in several assays, such as outcome devaluation, attentional set shifting and reversal learning, conditional responding, as well as delayed alternation to measure different aspects of executive functioning. Goal-directed behaviour per se was not different between ST and GT rats in the outcome devaluation task. ST rats performed slightly better than GT rats in one condition of the set shifting task (place->cue shift) and the delayed alternation task, but did not perform as well in the conditional responding task. Thus, differential behavioural performance between ST and GT rats was dependent on the specific task context. Further, we found evidence that the differences in executive functions are likely related to increased incentive salience attribution and impulsive action in ST rats.
Gesehen am 19.07.2019